Safety of Dabigatran as an Anticoagulant: A Systematic Review and Meta-Analysis - Zhou, Ya; Yao, Zhihao; Zhu, Linjie; Tang, Yong; Chen, Jie; Wu, Jianming (Frontiers in Pharmacology, 2021)
Background: Dabigatran is a univalent low-molecular-weight direct thrombin inhibitor (DTI), which was developed as an alternative to vitamin K antagonists (VKAs). However, the safety of dabigatran remains controversial so far. In this study, we aimed to compare the risk of bleeding, fatal adverse events, and the all-cause mortality of dabigatran with those of the control group by a systematic review and meta-analysis of randomized controlled trials (RCTs). Methods: We systematically searched PubMed, Web of Science, Cochrane Library, Medline, Embase, Wanfang database, Clinical trial, China National Knowledge Infrastructure (CNKI), Chinese Scientific Journal Database (VIP), and Chinese Biological Medicine Database (CBM), for clinical trials on conventional treatments compared with dabigatran, between January 2014 and July 2020. The reported outcomes, including the results of primary safety, were systematically investigated. Results: Seven RCTs (n=10,743) were included in the present systematic review. Compared to the control groups, dabigatran was not associated with an increased risk of major bleeding (relative risk [RR] 0.86, 95% confidence interval [CI]: 0.61 to 1.21, P=0.06), intracranial hemorrhage (RR 0.89, 95% CI: 0.58, 1.36, P=0.41), fatal adverse reactions (RR 0.87, 95% CI: 0.65 to 1.17, P=0.66), all-cause mortality (RR 0.88, 95% CI: 0.70 to 1.11, P=0.45, I2=0%), and significantly reduced risk of clinically relevant non-major bleeding (RR 0.96, 95% CI: 0.65 to 1.42, P=0.0007). However, dabigatran is associated with an increased risk of gastrointestinal (GI) bleeding (RR 1.78, 95% CI: 1.02 to 3.13, P=0.05). Conclusion: Dabigatran has a favorable safety profile in terms of major bleeding, intracranial hemorrhage, and life-threatening events, among other safety outcomes. The present study suggested that dabigatran may be a suitable alternative to VKAs as an oral anticoagulant. However, more data are necessary for clarifying the incidence of other adverse events and serious adverse reactions.